AKIBAT HUKUM PEMBATALAN AKTA NOTARIS BERDASARKAN PUTUSAN PENGADILAN DALAM SENGKETA PERDATA - Lubis, Fauziah; Putri, Deby Octafiani; Iwani, Syadzwina Rasyiah; Jelita, Retina Putri; Natalia, Tita Nazwa; Zakiva, Annisa Humayro; Fadilah, Rifai (IAIN Ambon, 2025)
This study aims to analyze the legal basis for the cancellation of a notarial deed and explain the legal consequences that arise on the status of the deed, the notary's responsibility, and the rights of the parties, as well as to examine legal protection for third parties in good faith. Cancellation of a notarial deed in a civil dispute is an important issue because the deed functions as authentic evidence with perfect evidentiary power. However, the deed can be canceled if there is a violation of the formal and material requirements according to the provisions of the Civil Code and Law Number 2 of 2014 concerning the Position of Notary. The research method used is normative juridical with an approach to statutory regulations, legal doctrine, and court decision studies. The results of the study show that the cancellation of the deed eliminates its authentic power and gives rise to civil, criminal, administrative, and ethical responsibilities for the notary, as well as having an impact on derivative agreements and the rights of third parties. Therefore, caution is needed in notarial practices as well as strengthening supervision and legal updates that are responsive to developments in the digital era. Keywords: cancellation of notarial deed, notary's responsibility, third party protection